TELURUL - METAL CU IMPLICAŢIE ENERGETICĂ (PANGEEA, 2025)
Tellurium - having power metal. This paper presents a mineral that is not common or well known, but may help the environment by employing its kind in the construction of solar panels, especially because it does not pollute. Tellurium, a mineral first found in our country and later spread to his qualities.